(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study aims to study the inheritance property rights in Kinnaur District of Himachal Pradesh. In this descriptive study researcher aims to identify the customs of not given property rights to Women of the Kinnaur. An important but uncommon cultural practice prevails in which woman doesn’t have rights on inheritance property. The custom of Kinnaura brotherly polyandry, in which a woman marries more than two brothers, is a sophisticated collective tactic that has helped people residing in hostile situations feel less apprehensive about their situation in life. There is a strong relationship between property rights and polyandry in Kinnaur.. Through the execution of a descriptive analysis and the semi-structure interview which examine these diverse parameters of women’s land rightsin Kinnaur. Scholars can get a thorough comprehension of polyandry and its importance in diverse sociocultural settings. Such study advances scientific awareness of various interpersonal traditions and multicultural tolerance.